THE POTENTIAL OF APATITE CARBONATE AS A SCAFFOLDING MATERIAL FOR TISSUE ENGINEERING IN THE TREATMENT OF ENDODONTIC REGENERATION : LITERATURE REVIEW - Ratih Widyasari; Ira Artilia; Nabila Wira Andhini (Jurnal EduHealth, 2022)
Endodontic regeneration treatment is a biological procedure designed to replace the biological structure of damaged teeth. Pulp tissue engineering in endodontic regeneration therapy combines three components, namely stem cells, scaffolds, and growth factors. Apatite carbonate has proven potential as a scaffold for bone regeneration. This study aimed to investigate the potential of apatite carbonate as a scaffold for the regeneration of the pulp dentin complex tissue. The method used is a literature study. Article searches, in English and Indonesian, were conducted through Sciencedirect and PubMed. The articles used are articles published in the last 10 years. The keywords used were endodontic regeneration, scaffolding, and carbonate apatite, then the articles were re-filtered according to the inclusion and exclusion criteria. A total of 12 literatures were included in this review. The results of data synthesis indicate that apatite carbonate is a biomaterial that has biocompatible properties and bioactivity to induce tissue regeneration, especially hard bone tissue. The stability of the material so that it can be modified to adjust its porous size and good biodegradability also supports its potential as a scaffold material. The material also has a chemical structure similar to bone and teeth, so it has the potential to induce the proliferation and differentiation of odontoblasts which are important in endodontic regeneration.